Bioinspired Approaches for Human-Centric Technologies - Cingolani, Roberto (Springer International Publishing : Imprint: Springer, 2014)
The present book discusses topics related to research and development of materials and devices at nanoscale size and their respective application in medicine and biomedicine. The individual chapters give a detailed state of the art overview to the distinct topic. Apparently disconnected fields - life sciences, biomedicine, chemistry, physics, medicine and engineering - are bridged with a highly interdisciplinary view onto each subject.